The Effect of Javanese Chili (Piper retrofractum) and Lemon (Citrus limon) Formula on Total Cholesterol Levels in Male White Rats - Setiani, Lusi Agus; Herlina, Nina; Ramadhani, Friska Noerfitria (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Hypercholesterolemia, defined as blood cholesterol levels exceeding 200 mg/dL, is a significant risk factor for cardiovascular disease. Traditional Indonesian medicinal plants, such as Javanese chili (Piper retrofractum) and lemon (Citrus limon), have long been recognized for their potential lipid-lowering properties. This study aimed to scientifically evaluate the hypocholesterolemic effect of a combined P. retrofractum and C. limon extract in a hypercholesterolemic rat model. Thirty male Sprague-Dawley rats were randomly assigned to seven groups: a normal control, a negative control (Na-CMC), a positive control (simvastatin 0.018 mg/200 g BW), a scientific herbal formula (0.18 g/200 g BW), and three treatment groups receiving P. retrofractum and C. limon in ratios of 1:1, 1:2, and 2:1. Hypercholesterolemia was induced using a cholesterol-cholate-thiouracil (CCT) mixture alongside a high-fat diet. Total cholesterol levels were quantified using the Cholesterol Oxidase-Peroxidase Aminoantipyrine (CHOD-PAP) method. After 21 days of treatment, all P. retrofractum and C. limon-treated groups demonstrated a statistically significant reduction in total cholesterol compared to the negative control (p <0.05). Notably, the 1:1 and 1:2 ratios of P. retrofractum to C. limon yielded the most substantial cholesterol reductions (44% and 43%, respectively), comparable to the scientific herbal formula and superior to simvastatin (30%). In contrast, the 2:1 ratio showed a comparatively lower reduction (38%), suggesting a potential inhibitory effect of excessive P. retrofractum on C. limon's lipid-lowering properties. These findings collectively highlight the promising potential of optimized P. retrofractum and C. limon combinations, particularly at 1:1 and 1:2 ratios, as effective natural interventions for managing hypercholesterolemia.